Pengembangan Media Pembelajaran Siklus Air Berbasis Digital Siswa Kelas V Sekolah Dasar - Lady Alfie; Sylvia Lara Syaflin; Kabib Sholeh (Elementary Teacher Education Program, Majalengka University, 2023)
This research was motivates by the students who are still difficult to understand material that is abstract in nature and the lack of utilization of learning media, because currently students abilities are quite good in digital access, the environment and facilities that have been complement. This study aims to producing a valid and practically of digital based water cycle learning media. The method used in this study is the ADDIE model. The subjects in this study were 5th students at SD Negeri Mardiharjo with 3 students on the one to one evaluation and 10 students on the small group evaluation. The data collection techniques used are interviews, observation and questionnaires. The instrument validation technique used is media, material adn language validation. The data analysis technique used is the validity and practicalitu analysis by the media. The results showed that the digital-based water cycle learning media developed in this study were very valid. There are three aspects influence the level of validity, which are the validity of the media, material and language. Furthermore, from those three validations, a validity value of 83.52% was obtained with the